A Randomized Effectiveness Trial of Interpersonal Psychotherapy for Depressed Women With Sexual Abuse Histories - Talbot, Nancy L. (2011)
OBJECTIVES: Many depressed women seen in community mental health centers (CMHCs) have histories of childhood sexual abuse and are economically disadvantaged. Randomized trials are needed to test the effectiveness of evidence-based interventions in this population and setting. This study compared interpersonal psychotherapy with usual care psychotherapy among women in a CMHC. METHODS: Among 1,100 women seeking treatment in a CMHC, 230 (21%) had major depression and histories of childhood sexual abuse. Seventy women with major depression and sexual abuse before age 18 were randomly assigned to interpersonal psychotherapy (N=37) or usual care psychotherapy (N=33). Staff clinicians provided all treatments. Participants were assessed at study entry and at ten, 24, and 36 weeks after random assignment. Generalized estimating equations were used to examine change over time. RESULTS: Compared with women assigned to usual care, women who received interpersonal psychotherapy had greater reductions in depressive symptoms (Hamilton Rating Scale, p=.05, d=.34; Beck Depression Inventory–II, p=.01, d=.29), posttraumatic stress disorder symptoms (p=.04, d=.76), and shame (p=.002, d=.38). Interpersonal psychotherapy and usual care yielded comparable improvements in social and mental health–related functioning. CONCLUSIONS: Interpersonal psychotherapy compared favorably to usual care psychotherapy in a CMHC in improving psychiatric symptoms and reducing shame among sexually abused women. However, there is a critical need for continued research to develop more effective treatments for the social and psychiatric sequelae of interpersonal trauma and socioeconomic disadvantage.